Analisis bakteri rhizosfer pelarut fosfat pada tanaman jagung dari wilayah Empang Sumbawa, NTB - Hidayati, Ernin; Okjayansah, Rosal; Faturrahman, Faturrahman; Suryadi, Bambang Fajar; Sarkono, Sarkono; Sukiman, Sukiman; Julisaniah, Nur Indah (Jurnal Biologi Udayana; Vol 28 No 1 (2024): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2024.v28.i01.p10, 2024)
Phosphate solubilizing bacteria are components of the soil ecosystem. They are play a pivotal role in supplying phosphate for plants. Exploration of phosphate solubilizing bacteria continues to be carried out to obtain potential isolates. This research aims to analyze phosphate solubilizing bacteria of maize rhizosphere plants in the Empang Sumbawa region, West Nusa Tenggara. The bacteria were isolated from the soil of  maize plants rhizosphere in the vegetative and generative growth phases. The ability of  solubilize phosphate of the isolates were tested using the spot inoculation technique on Pikovskaya Agar medium. The clear zone formed around the bacterial colony indicates the phosphate solubilization. A total of 18 isolates were successfully isolated. Eleven of them showed the ability to dissolving phosphate. The isolates V6 and V7 have the best performance, as indicated by phosphate dissolution index values of 1,3 and 1,54.